ECONOMIA CIRCULARĂ – UN MODEL DE PERSPECTIVĂ PENTRU REPUBLICA MOLDOVA - Bradu, Margareta (CEP USM, 2022)
In this article, we reveal the need for the transition to a new economic model, considering that the circular economy model would be more appropriate for the Republic of Moldova. Circular economy - is a model that aims to produce useful goods, with minimal negativ e effects on the environment and with the possibility of reproducing them. The circular economy model is based on innovations and innovative ideas, which lead to the development of the competitiveness of national economies, reduce the pressure on natural resources, develop competition and can drive sustainable economic growth. We analyze the ways and tools used in the European Union, which has a well -founded strategy in the targeted direction and considers itself a leader in this field. The hypothesis of th e proposed article is that, during the transition to the circular economy model, a new ecosystem will be formed, favorable for the development of innovative entrepreneurship and innovative companies.
CIRCULAR ECONOMY – A PERSPECTIVE MODEL FOR THE REPUBLIC OF MOLDOVA
Keywords: circular economy; sustainable economy; innovative entrepreneurship